Seropositivity for Trypanosoma cruzi in domestic dogs from Sonora, Mexico - Minerva Arce-Fonseca; Silvia C. Carrillo-Sánchez; Ramón M. Molina-Barrios; Mariana Martínez-Cruz; Jesús R. Cedillo-Cobián; Yuly A. Henao-Díaz; Olivia Rodríguez-Morales (BMC, 2017)
Abstract Background Chagas disease is an important health problem in Latin America due to its incapacitating effects and associated mortality. Studies on seropositivity for Trypanosoma cruzi in Mexican dogs have demonstrated a direct correlation between seropositivity in humans and dogs, which can act as sentinels for the disease in this region. The objective of this study was to determine the seropositivity for T.cruzi infection in dogs from Sonora, a northern borderstate of Mexico. Methods Responsible pet owners were selected at random from an urban area of Empalme municipality, Sonora, Mexico, and from there, 180 dog samples were collected. Anti-T. cruzi antibodies were determined using the enzyme-linked immunosorbent assay (ELISA) method. Reactive ELISA sera were processed by indirect immunofluorescence to confirm the presence of anti-T. cruzi antibodies. For the statistical analysis, chi-square tests were conducted. Results Dogs' sera showed a seropositivity rate of 4.44%. The rate of seropositivity was not associated with the dogs' age, sex, or socioeconomics pertaining to the geographical area. One sample (1/180, 0.55%) showed the acute state of the disease. Conclusions The study found a presence of anti-T. cruzi antibodies in dogs in this area, which suggests vector transmission. There is a need for active surveillance programs throughout the state of Sonora and vector control strategies should also be implemented in endemic regions.